Erythrocyte Sedimentation Rate Measurement Using as a Rapid Alternative to the Westergren Method - Hashemi, Reza; Majidi, Alireza; Motamed, Hassan; Amini, Afshin; Najari, Fares; Tabatabaey, Ali (Archives of Academic Emergency Medicine, 2018)
Introduction: Erythrocyte sedimentation rate (ESR) remains as one of the most reliable tests in clinical practices. Yet its use is time consuming and requires a large blood sample. The aim of this study was assessing a faster and reliable method of ESR estimation. Methods: An ESR estimation method was described and performed on 108 patients using capillary tube (micro ESR) and capillary peripheral blood. Micro ESR results at different intervals were measured and compared with Westergren ESR (conventional ESR) estimation by Pearson and Spearman’s coefficients. A regression equation was derived to predict conventional ESR values based on micro ESR results. The agreement of two measurements was demonstrated using the Bland-Altman plot. Results: Micro ESR results at 20 minutes showed the earliest close correlation with conventional ESR results at one hour (0.99). The presented regression equation was able to closely predict ESR values (r2 = 0.974) and the Bland-Altman plot showed an acceptable agreement between converted and conventional ESR measurements. Conclusion: Using capillary tube and capillary blood sample (micro ESR) appears to be a faster, cheaper, more reliable, and precise tool for ESR measurement in the ED. The results have acceptable correlation with conventional ESR, especially at 20 minutes of measurement.